Keputusan Pembelian Konsumen di ICI Koffie Madiun: Ditinjau dari Gaya Hidup dan Store Atmosphere - Moch. Zein Arrazi; Wahyu Prabawati Putri Handayani (MOTIVASI, 2025)
Purpose – This study aims to test and analyze the effect of lifestyle and store atmosphere on purchasing decisions for Ici koffie in Madiun. Design/methodology – The sample employed in this study comprised 100 respondents who are consumers of Ici Koffie in Madiun. The sampling technique utilized was purposive sampling. Data collection was conducted online through the use of Google Forms. The data analysis methods included validity and reliability testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, determination coefficient (R²) analysis, and t-tests. Findings - The findings indicate that the lifestyle variable exerts a significant positive influence on purchase decisions, while the store atmosphere variable also demonstrates a significant positive impact on purchase decisions. The coefficient of determination obtained is 0.789, suggesting that lifestyle and store atmosphere collectively account for 78.9% of the variance in purchase decisions, with the remaining 21.1% attributable to other factors not examined in this study.